Pemberdayaan Masyarakat Desa Suela Melalui Pengembangan Minuman Herbal Jahe Dan Cengkeh Sebagai Oleh-Oleh Khas Desa - Hasta Mitra Dewa; Quratul Puspa Aeni; Musta’an; Putri Wulandari; Nurrifta Zaitun; Putri Zahrina; Alya Cantika Khairunnisa; Yulianti Saputri; Gibran Bawafie; Tri Rachmanto (Universitas Mataram, 2026)
Suela Village is located in Suwela Subdistrict, East Lombok Regency, West Nusa Tenggara Province, Indonesia, which has natural resource potential in the form of spice commodities such as ginger and cloves. However, the utilization of these commodities is still limited and they are generally sold in raw form, resulting in relatively low economic added value for the community. This problem prompted the implementation of community service activities in Suela Village with the aim of empowering the community through the development of ginger and clove herbal drinks as souvenirs typical of the village. This activity was carried out using participatory methods, including socialization, training, and assistance to the community in the process of processing and packaging herbal beverage products. The results of this activity were ready-to-drink ginger and clove herbal beverages that have the potential to be developed as Suela Village's flagship products. In general, this activity is expected to open up new business opportunities and improve the economy and independence of the Suela Village community